Estimating and budgeting for large scale public sector projects - Tan, Yee Soon. (2008)
This dissertation is an attempt to understand the approaches to estimating and budgeting for large scale public sector projects, the different techniques used in cost estimating and to examine the factors and reasons for variances in estimates.